ISSUES OF ENHANCING THE LEGAL CULTURE OF TAXPAYERS IN IMPROVING TAX - Ikrom Ergashev (Journal of Legal Studies & Research, 2019)
The article deals with the formation of the legal culture of taxpayers and the promotion of the fulfillment of their tax obligations, it is important to implement educational programs related to taxes and tax payments, simplify tax legislation and tax administration, and ensure transparency of revenues and expenditures of the state budget.